Nano-composite microsphere supported copper catalytic material and preparation method and application thereof
By using nanocomposite microsphere-supported copper catalytic material (PS-CS-SiO2@Cu) to perform chiral asymmetric boron addition reaction, the problems of environmental pollution, harsh reaction conditions, high costs and catalyst recycling in the prior art are solved. , achieves efficient, environmentally friendly and economical catalytic effects, and is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411410871.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, there are problems such as serious environmental pollution, harsh reaction conditions, high costs, inability to recycle and use catalysts, and are not suitable for large-scale industrial production.
Nanocomposite microspheres are used to support copper catalytic materials, specifically through polystyrene/chitosan/silica nanocomposite microspheres (PS-CS-SiO2@Cu) as support, and copper acetate (Cu(OAc)2) , to achieve efficient catalysis of chiral asymmetric boron addition reaction, and to recover the catalyst through multiple cycles.
It realizes efficient catalytic chiral asymmetric boron addition reaction, and catalytic materials can be recycled and recycled multiple times, reducing production costs and reducing environmental pollution, and is suitable for large-scale industrial applications.
Smart Images

Figure CN119386928A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nanocomposite materials, and in particular to a nanocomposite microsphere-loaded copper catalytic material and a preparation method and application thereof. Background Art
[0002] Organoboron compounds are an important class of organic reaction intermediates. CB bonds can be converted into CC bonds, CN bonds, and CO bonds through reported reactions and are widely used in the synthesis of organic drugs. Therefore, how to efficiently construct CB bonds and synthesize chiral organoboron compounds is a hot topic for researchers. In 1988, Burgess et al. used cyclooctadiene rhodium chloride metal salt as a catalyst and DIOP or BINAP as a chiral ligand to achieve the first asymmetric boron addition, with an ee value of up to 76%; in 2019, Yun's group used chiral bisphosphine-linked CuCl as a catalyst and chiral N-heterocyclic carbene (NHC) as a chiral ligand, with a yield of 86% and an ee value of up to 96%.
[0003] Currently, it has been reported that boron addition reactions are mostly homogeneous catalysis, and the catalysts are difficult to recover and are not suitable for large-scale industrial applications. Other common metal catalytic ions Ag(I) and Pb(II) are prone to cause environmental pollution. Therefore, the development of a new catalytic material to achieve heterogeneous boron addition is of great significance. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a nanocomposite microsphere-loaded copper catalytic material and its preparation method and application, aiming to solve the technical problems existing in the prior art such as serious environmental pollution, harsh reaction conditions, high cost, inability to recycle the catalyst and unsuitability for large-scale industrial production.
[0005] In the first aspect, the present invention provides a nanocomposite microsphere-supported copper catalytic material, wherein the carrier of the catalytic material is PS-CS-SiO 2 Nanocomposite microspheres, PS-CS-SiO 2 Nanocomposite microspheres are composed of PS monodisperse microsphere powder, SiO 2 and chitosan, the active component of the catalytic material is Cu 2+ .
[0006] In the technical solution of the embodiment of the present application, the polystyrene (PS) monodisperse microsphere powder has the characteristics of small particle size, large specific surface area, strong adsorption, good dispersibility, easy modification and modification, and also exhibits good stability, strong hydrophobicity, low adhesion and other physical and chemical properties, and has low production cost; silica microspheres have the characteristics of controllable surface area, high mechanical strength, and stable thermal and physical and chemical properties. The control of silica surface structure can effectively improve the specific surface area of the microspheres, and has many micro-region-specific structural properties; chitosan has the advantages of wide availability, strong hydrophilicity, high metal ion binding activity, good biocompatibility, biodegradability and non-toxicity, and is an ideal adsorbent for organic synthesis catalysis. At the same time, chitosan has the advantages of Cu 2+ It has a high adsorption capacity and can achieve efficient catalysis under mild conditions, which is in line with the development concept of green chemistry.
[0007] PS-CS-SiO 2 @Cu catalytic materials have high catalytic activity for chiral asymmetric boron addition reactions. The catalytic materials can be recycled and reused multiple times while maintaining excellent performance, making them very suitable for large-scale industrial applications.
[0008] In a second aspect, the present invention provides a method for preparing a nanocomposite microsphere-supported copper catalytic material, comprising the following steps: S1. Prepare PS monodisperse microsphere powder in advance, mix PS monodisperse microsphere powder, hexadecyltrimethylammonium bromide, anhydrous ethanol and distilled water, stir to dissolve, add concentrated ammonia water and tetraethyl silicate, stir and mix evenly at room temperature, transfer to oil bath for heating, obtain white suspension, then reduce pressure and filter, wash the filter residue with anhydrous ethanol, and vacuum dry to obtain PS-SiO 2 powder; S2, chitosan powder, PS-SiO 2 The powder and aqueous acetic acid solution are mixed to obtain system A; S3, mixing sodium hydroxide, anhydrous ethanol and distilled water, stirring until colorless and clear, and cooling to room temperature to obtain system B; S4, adding system A dropwise into system B to form microspheres, filtering, washing with anhydrous ethanol, and drying at room temperature to obtain PS-CS-SiO 2 Nanocomposite microspheres; S5, in PS-CS-SiO 2 Cu loaded on nanocomposite microspheres 2+ , and obtain PS-CS-SiO 2 @Cu nanocomposite microspheres.
[0009] In the technical solution of the embodiment of the present application, the present application uses chitosan (CS) as a matrix, tetraethyl silicate (TEOS) as a silicon source, and hexadecyltrimethylammonium bromide (CTAB) as a surfactant to prepare PS-CS-SiO 2 Nanocomposite microspheres, PS-CS-SiO 2 The surface of the nanocomposite microspheres contains abundant functional groups, such as amino and hydroxyl groups, so they can be well complexed with metals. The material can be combined with copper salts through coordination bonds, has good catalytic effects, and can be stably recycled.
[0010] SiO 2 The Si-OH functional groups on the surface can react with the amino groups of chitosan to graft chitosan onto PS-SiO 2 PS-CS-SiO 2 Nanocomposite microspheres produce more complexing sites, which are convenient for subsequent coordination with copper ions; adding SiO 2 It can form abundant Si-OH on the surface of PS microspheres, enhance the hardness of the material, and make the microsphere structure more stable. 2 PS-CS-SiO 2 Nanocomposite microspheres have stable structure, cheap raw materials, low preparation cost, and are made of PS-CS-SiO 2 Nanocomposite microspheres were used as carriers to load copper acetate (Cu(OAc) 2 ), and obtain polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalyst (PS-CS-SiO 2 @Cu).
[0011] Preferably, the method for preparing PS monodisperse microsphere powder in step S1 comprises the following steps: S11. Add anhydrous ethanol to a reaction container, add 2.0-2.5 g of polyvinyl pyrrolidone, 0.4-0.6 g of azobisisobutyronitrile, 20-40 mL of styrene, and 2-5 mL of distilled water to every 80-100 mL of anhydrous ethanol, perform ultrasonic dispersion at room temperature for 0.5-1 h, stir for 18-30 h at 60-100° C. under inert gas protection to obtain a mixed solution; S12, centrifuging the mixed solution to obtain a precipitate, and washing the precipitate with anhydrous ethanol to obtain PS monodisperse microsphere powder.
[0012] In the technical solution of the embodiment of the present application, the polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalytic material (PS-CS-SiO 2@Cu), with styrene (St) as monomer, polyvinyl pyrrolidone (PVP) as surface stabilizer, growth modifier and dispersant, azobisisobutyronitrile (AIBN) as initiator, PS monodisperse microsphere powder was prepared. The prepared PS monodisperse microsphere powder had regular morphology and uniform microsphere particle size.
[0013] Preferably, in step S1, 0.8-1.0 g of hexadecyltrimethylammonium bromide, 100-150 mL of anhydrous ethanol and 80-120 mL of distilled water are added to every 0.8-1.2 g of PS monodisperse microsphere powder, and after stirring for 0.2-0.5 h, 0.5-1.0 mL of concentrated ammonia water and 0.5-0.8 mL of tetraethyl silicate are added, and the mixture is stirred at room temperature for 4-8 h, heated in an oil bath at 80 ° C for 10-18 h, and vacuum dried at 40-60 ° C for 10-18 h to obtain PS-SiO 2 powder.
[0014] Preferably, in step S2, 0.4-0.6 g PS-SiO is added to every 0.8-1.2 g chitosan. 2 powder and 102 mL of 1-5% v / v acetic acid aqueous solution; in step S3, 40-60 mL of anhydrous ethanol and 40-60 mL of distilled water are added to every 10.0-15.0 g of sodium hydroxide.
[0015] Preferably, in step S5, PS-CS-SiO 2 The preparation method of @Cu nanocomposite microspheres comprises the following steps: S51, the PS-CS-SiO obtained in step S4 2 The nanocomposite microspheres were placed in a water bath at 40-60°C for 1-2 h to obtain system C; S52, add 3.0-5.0 g of copper acetate per 40-60 mL of distilled water, stir at room temperature for 4-8 h to obtain system D; S53. Mix system C and system D without stirring, adsorb for 4 to 8 hours, filter, rinse with distilled water, and dry to obtain PS-CS-SiO2@Cu nanocomposite microspheres.
[0016] In the technical solution of the embodiment of the present application, PS-SiO 2 Nanocomposite microspheres have unique compatibility and spatial structure, and have a larger surface area than chitosan materials because chitosan is loaded onto PS-SiO 2 Microsphere surface, PS-SiO 2 The microspheres have a large specific surface area and make chitosan in PS-SiO 2The microspheres are evenly dispersed on the surface, exposing more complexing sites, thus significantly enhancing the complexing ability of copper and making it more fully in contact with the reaction substrate, thus achieving higher catalytic activity when preparing chiral organic boron compounds. 2 ), provides an alkaline environment for the reaction, and can realize catalytic reaction in a mixed solvent of organic reagent and water, which reduces the amount of organic reagent and alkali to a certain extent, and is in line with the concept of green chemistry development; in addition, the catalytic material can be recycled and reused many times and maintain excellent performance, which is very suitable for large-scale industrial application.
[0017] In a third aspect, the present application provides an application of a nanocomposite microsphere-supported copper catalytic material for preparing a chiral organic boron compound having the structural formula:
[0018] Where R 1 is phenyl or p-fluorophenyl, R 2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; The preparation method of the chiral organoboron compound comprises the following steps: P1, add 0.24mmol of biboric acid pinacol ester, 0.5~1.0mg of Bolm chiral ligand, PS-CS-SiO 2 @Cu nanocomposite microsphere catalyst 2.2~2.9mg and toluene (TL)-H 2 O mixed solvent 2mL, stirred for 10-14h, then filtered under reduced pressure, the filtrate and residue were set aside; P2, the filtrate was extracted with ethyl acetate and saturated brine, and then with anhydrous Na 2 SO 4 The organic phase was dried, filtered under reduced pressure and rotary dried to obtain a crude product; P3, purifying the crude product by thin layer chromatography to obtain a chiral organic boron compound; The reaction substrate structure in step P1 is as follows:
[0019] Where R 1 is phenyl or p-fluorophenyl, R 2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; P4. Wash the filter residue with petroleum ether, dry it in vacuum, and then recover the nanocomposite microsphere-loaded copper catalyst for recycling.
[0020] Preferably, the structural formula of the Bolm chiral ligand in step P1 is: .
[0021] In a fourth aspect, the present application provides an application of a nanocomposite microsphere-supported copper catalytic material for preparing a chiral hydroxyl compound having the structural formula:
[0022] Where R 1 is phenyl or p-fluorophenyl, R 2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; The preparation method of the chiral hydroxy compound comprises the following steps: (1) Add 240-250 mg of sodium borate tetrahydrate and tetrahydrofuran (THF)-H to the chiral organic boron compound obtained in step P3. 2 O mixed solvent 5mL, stirred for 3~6h, extracted with ethyl acetate and saturated brine, and then washed with anhydrous Na 2 SO 4 Dry the organic phase, filter under reduced pressure and spin dry; (2) The residue is spin-dried and purified by thin layer chromatography to obtain a chiral hydroxy compound.
[0023] Preferably, in step (1), THF-H 2 O mixed solvent V(THF):V(H 2 O)=3:2.
[0024] Preferably, the developing solvent used for thin layer chromatography in step (2) is a mixed solvent of petroleum ether (PE) and ethyl acetate (EA), wherein the volume ratio of PE:EA is 5:1.
[0025] Different from the existing technical solutions, the beneficial effects of this application include: 1. PS-CS-SiO 2 @SiO in Cu catalytic materials 2 Contains silanol, which can react with the amino group of chitosan to form a condensation reaction. 2 It can form abundant Si-OH on the surface of PS microspheres, enhance the hardness of the material, make the microsphere structure more stable, and the Si-OH functional groups on the surface can also react with the amino groups of chitosan to produce more complexing sites, which are convenient for subsequent coordination with copper ions. 2 PS-CS-SiO 2 Nanocomposite microspheres have stable structure, cheap raw materials, low preparation cost, and are made of PS-CS-SiO 2 Nanocomposite microspheres were used as carriers to load copper acetate (Cu(OAc) 2), and obtain polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalyst (PS-CS-SiO 2 @Cu).
[0026] 2. The polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalytic material (PS-CS-SiO 2 @Cu) has good biocompatibility, is green and environmentally friendly, and is easy to operate. After the reaction is completed, the catalyst can be easily separated from other components in the reaction system by common solid-liquid separation methods, which greatly reduces the production cost and realizes the polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalytic materials (PS-CS-SiO 2 @Cu) can be recycled multiple times, and various environmental pollution problems can be significantly reduced.
[0027] 3. Using the polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalytic material (PS-CS-SiO 2 @Cu) as a catalyst, the spherical structure of the catalyst surface has more active contact sites than the traditional powdered catalyst. Therefore, under the same conditions, the required amount of catalyst is lower, the reaction conditions are mild, it can be carried out at room temperature, and it is simple and easy to operate.
[0028] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 PS raw material, PS-CS-SiO 2 Nanocomposite microspheres and PS-CS-SiO 2 @Infrared spectrum of Cu catalyst; Figure 2 This is the SEM image of PS raw material (magnification is 2000 times); Figure 3 PS-CS-SiO 2 SEM image of nanocomposite microspheres (magnification 8000 times); Figure 4PS-CS-SiO 2 @SEM image of Cu catalyst (magnification 8000 times). DETAILED DESCRIPTION
[0031] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0033] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0034] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0035] It has been reported that boron addition reactions are mostly homogeneous catalysis, the catalysts are difficult to recover, and are not suitable for large-scale industrial applications. Common metal catalytic ions Cu(II), Ag(I) and Pb(II) are all heavy metal ions, and large-scale use can easily cause environmental pollution.
[0036] In order to solve the technical problems in the prior art such as serious environmental pollution, harsh reaction conditions, high cost, inability to recycle catalysts, and unsuitability for large-scale industrial production, the present application provides a preparation method and application of nanocomposite microsphere-supported copper catalytic materials, wherein the polystyrene / chitosan / silicon dioxide nanocomposite microsphere-supported copper catalytic material (PS-CS-SiO 2@Cu) catalyzes the boron addition reaction. The catalytic material has good biocompatibility, is green and environmentally friendly, and is easy to operate. After the reaction is completed, the catalyst can be easily separated from other components in the reaction system by using common solid-liquid separation methods, which greatly reduces the production cost and realizes the polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalytic material (PS-CS-SiO 2 @Cu) can be recycled multiple times, and various environmental pollution problems can be significantly reduced.
[0037] In the first aspect, the present invention provides a nanocomposite microsphere-supported copper catalytic material, wherein the carrier of the catalytic material is PS-CS-SiO 2 Nanocomposite microspheres, PS-CS-SiO 2 Nanocomposite microspheres are composed of PS monodisperse microsphere powder, SiO 2 and chitosan, the active component of the catalytic material is Cu 2+ .
[0038] In a second aspect, the present invention provides a method for preparing a nanocomposite microsphere-supported copper catalytic material, comprising the following steps: S1. Prepare PS monodisperse microsphere powder in advance, mix PS monodisperse microsphere powder, hexadecyltrimethylammonium bromide, anhydrous ethanol and distilled water, stir to dissolve, add concentrated ammonia water and tetraethyl silicate, stir and mix evenly at room temperature, transfer to oil bath for heating, obtain white suspension, then reduce pressure and filter, wash the filter residue with anhydrous ethanol, and vacuum dry to obtain PS-SiO 2 powder; S2, chitosan powder, PS-SiO 2 The powder and acetic acid aqueous solution are mixed to obtain system A; S3, mixing sodium hydroxide, anhydrous ethanol and distilled water, stirring until colorless and clear, and cooling to room temperature to obtain system B; S4, adding system A dropwise into system B to form microspheres, filtering through a mesh, washing with anhydrous ethanol, and drying at room temperature to obtain PS-CS-SiO 2 Nanocomposite microspheres; S5, in PS-CS-SiO 2 Cu loaded on nanocomposite microspheres 2+ , and obtain PS-CS-SiO 2 @Cu nanocomposite microspheres.
[0039] Preferably, the method for preparing PS monodisperse microsphere powder in step S1 comprises the following steps: S11, add 2.0-2.5 g of polyvinyl pyrrolidone, 0.4-0.6 g of azobisisobutyronitrile, 20-40 mL of styrene, and 2-5 mL of distilled water to every 80-100 mL of anhydrous ethanol, perform ultrasonic dispersion at room temperature for 0.5-1 h, stir for 18-30 h at 60-100 °C under inert gas protection to obtain a mixed solution; S12, centrifuging the mixed solution to obtain a precipitate, and washing the precipitate with anhydrous ethanol to obtain PS monodisperse microsphere powder.
[0040] Preferably, in step S1, 0.8-1.0 g of hexadecyltrimethylammonium bromide, 100-150 mL of anhydrous ethanol and 80-120 mL of distilled water are added to every 0.8-1.2 g of PS monodisperse microsphere powder, and after stirring for 0.2-0.5 h, 0.5-1.0 mL of concentrated ammonia water and 0.5-0.8 mL of tetraethyl silicate are added, and the mixture is stirred at room temperature for 4-8 h, heated in an oil bath at 80 ° C for 10-18 h, and vacuum dried at 40-60 ° C for 10-18 h to obtain PS-SiO 2 powder.
[0041] Preferably, in step S2, 0.4-0.6 g PS-SiO is added to every 0.8-1.2 g chitosan. 2 powder and 102 mL of 1-5% v / v acetic acid aqueous solution; in step S3, 40-60 mL of anhydrous ethanol and 40-60 mL of distilled water are added to every 10.0-15.0 g of sodium hydroxide.
[0042] Preferably, in step S5, PS-CS-SiO 2 The preparation method of @Cu nanocomposite microspheres comprises the following steps: S51, placing the PS-CS-SiO2 nanocomposite microspheres obtained in step S4 in a water bath at 40-60°C for 1-2 hours to obtain system C; S52, add 3.0-5.0 g of copper acetate per 40-60 mL of distilled water, stir at room temperature for 4-8 h to obtain system D; S53, system C and system D were mixed without stirring, adsorbed for 4-8 hours, filtered, rinsed with distilled water, and dried to obtain PS-CS-SiO 2 @Cu nanocomposite microspheres.
[0043] In the technical solution of the embodiment of the present application, the PS-CS-SiO 2 @Cu, chitosan to Cu 2 + The adsorption is mainly based on amino coordination complex (formula b), and the main adsorption reactions include: a. Amino group (-NH 2 ) Protonation: -NH 2 + H+ ↔ -NH 3 + b. Amino group (-NH 2 )Coordination complex: -NH 2 + Cu 2+ ↔ -NH 2 ·Cu 2+ c. Hydrogen bond adsorption: -NH 2 + OH - ↔ -NH 2 OH - d. Electrostatic attraction: -NH 3 + + CuOH + ↔ -NH 3 + ·CuOH + When the pH of the reaction system is low, the amino group (-NH 2 ) participates in the protonation reaction to form -NH 3 + More, and the amino group (-NH 2 ) is less, Cu 2+ The complexation with chitosan is weak, and this application uses copper acetate as Cu 2+ Source, copper acetate solution is weakly alkaline, which is conducive to Cu 2+ Complexed with chitosan.
[0044] The PS-CS-SiO 2 PS monodisperse microsphere powder was prepared using styrene (St) as monomer, polyvinyl pyrrolidone (PVP) as surface stabilizer, growth modifier and dispersant, and azobisisobutyronitrile (AIBN) as initiator. Then, PS-CS-SiO was prepared using chitosan (CS) as matrix, tetraethyl silicate (TEOS) as silicon source, and cetyltrimethylammonium bromide (CTAB) as surfactant. 2 Nanocomposite microspheres were used as carriers to load copper acetate (Cu(OAc) 2 ), and obtain polystyrene / chitosan / silicon dioxide nanocomposite microspheres loaded with copper catalyst (PS-CS-SiO 2 @Cu).
[0045] In a third aspect, the present application provides an application of a nanocomposite microsphere-supported copper catalytic material for preparing a chiral organic boron compound having the structural formula:
[0046] Where R1 is phenyl or p-fluorophenyl, R 2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; The preparation method of the chiral organoboron compound comprises the following steps: P1, add 0.24mmol of biboric acid pinacol ester, 0.5~1.0mg of Bolm chiral ligand, PS-CS-SiO 2 @Cu nanocomposite microsphere catalyst 2.2~2.9mg and TL-H 2 O mixed solvent 2mL, stirred for 10-14h, then filtered under reduced pressure, the filtrate and residue were set aside; P2, the filtrate was extracted with ethyl acetate and saturated brine, and then with anhydrous Na 2 SO 4 The organic phase was dried, filtered under reduced pressure and rotary dried to obtain a crude product; P3, purifying the crude product by thin layer chromatography to obtain a chiral organic boron compound; The reaction substrate structure in step P1 is as follows:
[0047] Where R 1 is phenyl or p-fluorophenyl, R 2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; P4. Wash the filter residue with petroleum ether, dry it in vacuum, and then recover the nanocomposite microsphere-loaded copper catalyst for recycling.
[0048] Preferably, the structural formula of the Bolm chiral ligand in step P1 is: .
[0049] In a fourth aspect, the present application provides an application of a nanocomposite microsphere-supported copper catalytic material for preparing a chiral hydroxyl compound having the structural formula:
[0050] Where R 1 is phenyl or p-fluorophenyl, R 2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; The preparation method of the chiral hydroxy compound comprises the following steps: (1) Add 240-250 mg of sodium borate tetrahydrate and THF-H to the chiral organic boron compound obtained in step P3. 2 O mixed solvent 5mL, stirred for 3~6h, extracted with ethyl acetate and saturated brine, and then washed with anhydrous Na 2 SO4 Dry the organic phase, filter under reduced pressure using a sand core funnel and spin dry; (2) The residue is spin-dried and purified by thin layer chromatography to obtain a chiral hydroxy compound.
[0051] Preferably, in step (1), THF-H 2 O mixed solvent V(THF):V(H 2 O)=3:2.
[0052] Preferably, the developing solvent used for thin layer chromatography in step (2) is a mixed solvent of PE and EA, wherein the volume ratio of PE:EA is 5:1.
[0053] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0054] 1. Preparation method Example 1 PS-CS-SiO 2 The preparation method of @Cu catalytic material comprises the steps of: (1) Preparation of PS monodisperse microsphere powder S1, add 2.25g polyvinyl pyrrolidone, 0.5g azobisisobutyronitrile, 30mL styrene, 95mL anhydrous ethanol and 3mL distilled water into the reaction bottle, and ultrasonically disperse at room temperature for 0.5h; S2, in N 2 Under inert gas protection, stir at 70 °C for 24 h; S3. Centrifuge and wash with anhydrous ethanol several times to obtain PS monodisperse microsphere powder.
[0055] (2) PS-SiO 2 Powder preparation S1. Add 1.0 g PS monodisperse microsphere powder, 0.92 g hexadecyltrimethylammonium bromide, 120 mL anhydrous ethanol and 100 mL distilled water to a reaction bottle, stir and dissolve for 20 min, then quickly add 0.8 mL concentrated ammonia and 0.6 mL tetraethyl silicate, stir at room temperature for 6 h, then transfer to an oil bath at 80 ° C and heat for 12 h to obtain a white suspension; S2, vacuum filter, wash with anhydrous ethanol several times, and vacuum dry at 50 ° C for 12 h to obtain PS-SiO 2 White fluffy powder.
[0056] (3) PS-CS-SiO2 Preparation of nanocomposite microspheres S1. Add 1.0g chitosan (CS) powder and 0.5g PS-SiO 2 powder and 100 mL of 1% v / v acetic acid aqueous solution to obtain System A; S2. Add 12.0 g of sodium hydroxide, 50 mL of anhydrous ethanol and 50 mL of distilled water to the reaction bottle, stir until colorless and clear, and cool to room temperature to obtain system B; S3, using a syringe to drip system A into system B, filter through a mesh, wash with anhydrous ethanol several times, and dry at room temperature to obtain PS-CS-SiO 2 Nanocomposite microspheres.
[0057] (4) PS-CS-SiO 2 Preparation of @Cu nanocomposite microspheres S1, the obtained 1.0gPS-CS-SiO 2 The nanocomposite microspheres were placed in a reaction bottle in a water bath at 50°C for 1 h to obtain system C; S2. Add 3.7 g of copper acetate and 50 mL of distilled water to the reaction bottle and stir at room temperature for 6 h to obtain system D; S3, the system C and the system D were stirred and mixed, adsorbed for 5 hours, filtered through a mesh, rinsed with distilled water, and dried at 50°C for 12 hours to obtain PS-CS-SiO 2 @Cu nanocomposite microspheres.
[0058] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no SiO is added to the catalytic material. 2 : PS-CS-SiO 2 The preparation method of @Cu catalytic material comprises the steps of: (1) Preparation of PS monodisperse microsphere powder S1, add 2.25g polyvinyl pyrrolidone, 0.5g azobisisobutyronitrile, 30mL styrene, 95mL anhydrous ethanol and 3mL distilled water into the reaction bottle, and ultrasonically disperse at room temperature for 0.5h; S2, in N 2 Under inert gas protection, stir at 70 °C for 24 h; S3. Centrifuge and wash with anhydrous ethanol several times to obtain PS monodisperse microsphere powder.
[0059] (2) Preparation of PS-CS nanocomposite microspheres S1, add 1.0 g chitosan (CS) powder, 0.5 g PS powder and 100 mL 1% v / v acetic acid aqueous solution into a reaction bottle to obtain system A; S2. Add 12.0 g of sodium hydroxide, 50 mL of anhydrous ethanol and 50 mL of distilled water to the reaction bottle, stir until colorless and clear, and cool to room temperature to obtain system B; S3. Use a syringe to drop system A into system B, filter through a mesh, wash with anhydrous ethanol for several times, and dry at room temperature to obtain PS-CS nanocomposite microspheres.
[0060] (3) Preparation of PS-CS@Cu nanocomposite microspheres S1, placing 1.0 g of the obtained PS-CS nanocomposite microspheres in a reaction bottle in a water bath at 50° C. for 1 h to obtain system C; S2. Add 3.7 g of copper acetate and 50 mL of distilled water to the reaction bottle and stir at room temperature for 6 h to obtain system D; S3. Stir and mix system C and system D, adsorb for 5 h, filter through a mesh, rinse with distilled water, and dry at 50 °C for 12 h to obtain PS-CS@Cu nanocomposite microspheres.
[0061] Example 2 The PS-CS-SiO obtained in Example 1 2 @Cu nanocomposite microsphere catalytic material is applied to chiral asymmetric boron addition reaction, including the following steps: S1. Add 0.2 mmol chalcone (Compound I) and 0.24 mmol pinacol diboronate (B 2 (pin) 2 )、0.5Bolm chiral ligand, 2mL TL-H 2 O (V:V = 1:9) mixed solvent and 1.4 mg of PS-CS-SiO prepared in Example 1 2 @Cu, stir at room temperature for 10~14h, α , β The asymmetric borylation reaction of unsaturated ketones has the following reaction equation:
[0062] S2, after the above reaction is completed, the filtrate and the residue are ready for use; S3, the filtrate was extracted 3 times with ethyl acetate (EA), 2 times with saturated brine, and 2 SO 4 The organic phase was dried, filtered under reduced pressure using a sand core funnel and rotary dried to remove excess ethyl acetate (EA) to obtain a crude product; S4, purifying the crude product by thin layer chromatography (TLC) to obtain a chiral organic boron compound (Compound II); S5. Take the filter residue obtained in step S2 above, wash it with petroleum ether (PE) three times, and dry it under vacuum at 50°C for 15h to remove the petroleum ether (PE), and recover PS-CS-SiO 2 @Cu catalytic material is recycled.
[0063] Example 3 The difference between Example 3 and Example 2 is that in step S1, PS-CS-SiO 2 @The amount of Cu catalytic material added is 2.2 mg.
[0064] Example 4 The difference between Example 4 and Example 2 is that in step S1, PS-CS-SiO 2 @The added amount of Cu catalytic material is 2.9 mg.
[0065] Example 5 The difference between Example 5 and Example 2 is that in step S1, PS-CS-SiO 2 @The amount of Cu catalytic material added is 4.3 mg.
[0066] Example 6 The PS-CS-SiO obtained in Example 4 2 @Cu nanocomposite microsphere catalytic material is used in chiral asymmetric boron addition reaction and expansion of reaction substrates, including the following steps: S1, add the reaction substrate 0.2mmol compound IV-1, 0.24mmol biboric acid pinacol ester (B 2 (pin) 2 ), 0.5 mg Bolm chiral ligand, 2.9 mg PS-CS-SiO prepared in Example 1 2 @Cu and 2mL TL-H 2 O (V:V = 1:9) mixed solvent, stirred at room temperature for 12h, α , β The asymmetric borylation reaction of unsaturated ketones has the following reaction equation:
[0067] The structural formula of compound IV-1 is as follows:
[0068] S2, after the above reaction is completed, the filtrate and the residue are ready for use; S3, the filtrate was extracted 3 times with ethyl acetate (EA), 3 times with saturated brine, and then with anhydrous Na 2 SO 4The organic phase was dried, filtered under reduced pressure using a sand core funnel and rotary dried to remove excess ethyl acetate (EA) to obtain a crude product; S4, purifying the crude product by thin layer chromatography (TLC) to obtain a chiral organoboron compound (Compound V); The structural formula of the obtained compound V-1 is as follows:
[0069] S5. Take the filter residue obtained in step S2 above, wash it with petroleum ether (PE) 33 times, and dry it under vacuum at 50°C for 15h to remove the petroleum ether (PE), and recover PS-CS-SiO 2 @Cu catalytic material recycling; The chiral organoboron compound (Compound V) obtained in the above step S4 is further converted into the corresponding chiral hydroxy compound (Compound III) by oxidation for determining the enantioselectivity and stereochemical configuration, comprising the following steps: S6. Add 240 mg of sodium borate tetrahydrate (NaBO 3 ·4H 2 O) and 5 mL THF-H 2 O (V:V = 3:2) mixed solvent, stirred at room temperature for 3-6h; S7. After the above reaction, the mixture was extracted with ethyl acetate (EA) for 3 times, saturated brine for 3 times, and anhydrous Na 2 SO 4 Dry the organic phase, filter under reduced pressure using a sand core funnel and spin dry to remove excess ethyl acetate (EA); S8. The residue was spin-dried and purified by thin layer chromatography (TLC) using a PE:EA=5:1 mixed solvent to obtain a chiral hydroxy compound (Compound VI). The reaction equation is as follows:
[0070] Example 7 The difference between Example 7 and Example 6 is that the reaction substrate added in step S1 is compound IV-2, and the structural formula of compound IV-2 is as follows:
[0071] The chiral organic boron compound prepared is compound V-2, and the structural formula is as follows:
[0072] Example 8 The difference between Example 8 and Example 6 is that the reaction substrate added in step S1 is compound IV-3, and the structural formula of compound IV-3 is as follows:
[0073] The chiral organoboron compound prepared is compound V-3, and the structural formula is as follows:
[0074] Example 9 The difference between Example 9 and Example 6 is that the reaction substrate added in step S1 is compound IV-4, and the structural formula of compound IV-4 is as follows:
[0075] The chiral organoboron compound prepared is compound V-4, and the structural formula is as follows:
[0076] Example 10 The PS-CS-SiO obtained in Example 1 2 @Cu nanocomposite microsphere catalytic material is applied to chiral asymmetric boron addition reaction, including the following steps: S1. Add 0.2 mmol chalcone (Compound I) and 0.24 mmol pinacol diboronate (B 2 (pin) 2 ), 0.5 mg Bolm chiral ligand, 2.9 mg PS-CS-SiO prepared in Example 1 2 @Cu and 2mL TL-H 2 O (V:V = 1:9) mixed solvent, stirred at room temperature for 12h, α , β The asymmetric borylation reaction of unsaturated ketones has the following reaction equation:
[0077] S2, after the above reaction is completed, the filtrate and the residue are ready for use; S3, the filtrate was extracted 3 times with ethyl acetate (EA), 3 times with saturated brine, and then with anhydrous Na 2 SO 4 The organic phase was dried, filtered under reduced pressure using a sand core funnel and rotary dried to remove excess ethyl acetate (EA) to obtain a crude product; S4, purifying the crude product by thin layer chromatography (TLC) to obtain a chiral organic boron compound (Compound II); S5. Take the filter residue obtained in step S2 above, wash it with petroleum ether (PE) three times, and dry it under vacuum at 50°C for 15 h to remove the petroleum ether (PE), and recover PS-CS-SiO 2 @Cu catalytic material recycling; The chiral organoboron compound (Compound II) obtained in the above step S4 is further converted into the corresponding chiral hydroxy compound (Compound III) by oxidation for determining the enantioselectivity and stereochemical configuration, comprising the following steps: S6. Add 240 mg of sodium borate tetrahydrate (NaBO 3 ·4H 2 O) and 5 mL THF-H 2 O (V:V = 3:2) mixed solvent, stirred at room temperature for 3-6 h; S7. After the above reaction, the mixture was extracted with ethyl acetate (EA) for 3 times, saturated brine for 3 times, and anhydrous Na 2 SO 4 Dry the organic phase, filter under reduced pressure using a sand core funnel and spin dry to remove excess ethyl acetate (EA); S8. The residue was spin-dried and purified by thin layer chromatography (TLC) using a PE:EA=5:1 mixed solvent to obtain a chiral hydroxy compound (Compound III). The reaction equation is as follows: Embodiment 11 The difference between Example 11 and Example 10 is that the catalyst used in step S1 in Example 11 is the catalyst recycled in S5 in Example 10, and the number of cycles is 1.
[0078] Example 12 The difference between Example 12 and Example 10 is that the catalyst used in step S1 in Example 12 is the catalyst recycled in S5 in Example 11, and the number of cycles is 2.
[0079] Embodiment 13 The difference between Example 13 and Example 10 is that the catalyst used in step S1 in Example 13 is the catalyst recycled in S5 in Example 12, and the number of cycles is 3.
[0080] Embodiment 14 The difference between Example 14 and Example 10 is that the catalyst used in step S1 in Example 14 is the catalyst recycled in S5 in Example 13, and the number of cycles is 4.
[0081] Embodiment 15 The difference between Example 15 and Example 10 is that the catalyst used in step S1 in Example 15 is the catalyst recycled in S5 in Example 14, and the number of cycles is 5.
[0082] Example 16 The difference between Example 16 and Example 10 is that the catalyst used in step S1 in Example 16 is the catalyst recycled in S5 in Example 15, and the number of cycles is 6.
[0083] 2. Test Method Yield and enantioselectivity (ee value) detection method of chiral organic boron compound: The crude product of chiral organic boron compound is oxidized by sodium perborate tetrahydrate oxidation system to obtain hydroxyl compound for separation, and finally the final product is obtained by column chromatography, and its structure and yield are determined by nuclear magnetic resonance, and then its enantioselectivity is tested by liquid chromatography analyzer.
[0084] 3. Analysis of test results of various examples and comparative examples (1) The PS monodisperse microsphere powder and PS-CS-SiO prepared in Example 1 were 2 Nanocomposite microspheres and PS-CS-SiO 2 @Cu nanocomposite microspheres were scanned by infrared spectra, and PS-CS-SiO 2 @Cu nanocomposite microspheres were scanned by SEM.
[0085] Figure 1 PS raw material, PS-CS-SiO 2 Nanocomposite microspheres and PS-CS-SiO 2 @Cu catalyst infrared spectrum; compared with the infrared spectrum of PS, in PS-CS-SiO 2 Some new absorption peaks appeared in the infrared spectrum of 740cm -1 The symmetrical stretching vibration absorption peak of Si-C is 438 cm -1 The bending vibration absorption peak of Si-O-Si can confirm that PS-CS-SiO 2 The microspheres were successfully prepared. 2 @Cu in the infrared spectrum at 1551cm -1 It is the vibration absorption peak of the amide II group in chitosan, 1046cm -1 The stretching vibration absorption peak and bending vibration absorption peak of the CH bond of copper acetate are shown in Figure 2. 2 The microspheres were successfully loaded with copper ions.
[0086] The prepared PS monodisperse microsphere powder is as follows Figure 2 As shown in the figure, the PS microspheres are uniform in size and can be well dispersed, and can be better used as carriers to load materials; the prepared PS-CS-SiO 2 Nanocomposite microspheres Figure 3 As shown in the figure, it can be seen that SiO 2It can be well loaded on PS microspheres, and the size of the microspheres is uniform; the prepared PS-CS-SiO 2 @Cu nanocomposite microspheres Figure 4 As shown in the figure, it can be seen that the morphology of the chitosan-based silica microspheres can be well maintained, and loaded particles, namely copper ion loads, can be seen on the surface.
[0087] (2) Different PS-CS-SiO 2 @Cu catalytic material dosage for chiral asymmetric boron addition reaction, comparative example 1 is the chiral asymmetric boron addition reaction using PS-CS@Cu catalytic material, the yield (yield) and enantioselectivity (ee value) of the chiral organic boron compound finally prepared are shown in the following Table 1: Table 1 Yields and enantioselectivities of chiral organoboron compounds prepared with different catalyst dosages
[0088] From the data in Table 1, it can be seen that when the reaction time is 12 h and the reaction solvent ratio is V(TL):V(H 2 O)=1:9, the change of catalyst dosage has a significant effect on the yield (yield) and enantioselectivity (ee value) of chiral asymmetric boron addition reaction. When the catalyst dosage is 1.4mg, the yield (yield) is only 64%, and the conversion effect is not good; when the catalyst dosage is 2.2mg, the yield (yield) is 90%, the enantioselectivity (ee value) is 93%, and the conversion effect and chirality are significantly improved; when the catalyst dosage is 2.9mg, the yield (yield)>99%, the enantioselectivity (ee value) is 94%, relative to the catalyst dosage of 2.2mg, the increase of 0.7mg catalyst has a significant effect on the yield (yield) and the enantioselectivity (ee value) remains at a high level; when the catalyst dosage is 4.3mg, the yield (yield) is 90%, the enantioselectivity (ee value) is 94%, which is not as good as the conversion effect when the catalyst dosage is 2.9mg. In summary, due to economic factors and other considerations, among the four groups of catalyst dosages shown in Table 1, 2.9 mg is the optimal reaction catalyst dosage when the reaction solvent ratio and reaction time are the same.
[0089] The catalytic material of Comparative Example 1 does not contain SiO 2 Therefore, the catalytic material does not contain Si hydroxyl groups, which cannot react with the amino groups of chitosan, and chitosan cannot be successfully loaded, resulting in the subsequent Cu 2+ The complexing effect is not good and the catalytic effect is poor. Under the same catalytic conditions, the yield is only 28%.
[0090] (3) In Examples 6 to 9, chiral asymmetric boron addition reactions were carried out on different reaction substrates. The yields (yield) and enantioselectivities (ee values) of the chiral organoboron compounds finally prepared are shown in Table 2 below: Table 2 Yields and enantioselectivities of chiral organoboron compounds prepared from different reaction substrates
[0091] From the data in Table 2, it can be seen that under the optimal reaction conditions, the extended substrate test was carried out and it was found that the PS-CS-SiO prepared in Example 1 2 @Cu catalytic materials have excellent universality. When the reaction substrate is ( E )-1-(4-fluorophenyl)-3-thiophen-2-ylprop-2-en-1-one, the yield was as high as 79% and the enantioselectivity was as high as 95%. E )-3-(naphthalen-2-yl)-1-phenylprop-2-en-1-one, the yield (yield) was 84%, and the enantioselectivity (ee value) was 97%; the substrate was ( E )-3-(3-bromophenyl)-1-phenylprop-2-en-1-one, the yield (yield) was as high as 95%, and the enantioselectivity (ee value) was as high as 92%; the substrate was ( E )-1-phenyl-3-p-tolylprop-2-en-1-one, the yield (yield) was as high as 95%, and the enantioselectivity (ee value) was as high as 94%. In summary, the PS-CS-SiO prepared in Example 1 2 @Cu catalytic materials are generally applicable to chiral asymmetric boron addition reactions of chalcone (compound I) and its derivatives.
[0092] (4) In Examples 10 to 16, the chiral asymmetric boron addition reaction was carried out using catalysts with different cycle times. The yields (yield) and enantioselectivities (ee values) of the chiral organoboron compounds finally prepared are shown in Table 3 below: Table 3 Effect of catalyst recycling times on the yield and enantioselectivity of organic boron compounds
[0093] From the data in Table 3, it can be seen that when the reaction time is 12 h and the reaction solvent ratio is V(TL):V(H 2O)=1:9, the catalyst dosage is the same as 2.9mg, and the number of times the catalyst is recycled has almost no effect on the yield (yield) and enantioselectivity (ee value) of the chiral asymmetric boron addition reaction. The catalyst that was not recycled and the catalyst that was recycled 6 times both had a yield (yield) and enantioselectivity (ee value) of more than 90%, and almost achieved complete conversion. This shows that the catalytic effect of the recycled catalyst is still significant, and the performance of the recycled catalyst is good, achieving the purpose of recycling, saving costs and responding to the concept of green chemistry development.
[0094] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A nanocomposite microsphere-supported copper catalytic material, characterized in that: The carrier of the catalytic material is PS-CS-SiO2 nanocomposite microspheres, which are composed of PS monodisperse microsphere powder, SiO2 and chitosan. The loaded active component of the catalytic material is Cu 2+ .
2. The method for preparing a nanocomposite microsphere-supported copper catalytic material according to claim 1, characterized in that: The following steps are involved: S1. Prepare PS monodisperse microsphere powder in advance, mix PS monodisperse microsphere powder, hexadecyltrimethylammonium bromide, anhydrous ethanol and distilled water, stir to dissolve, add concentrated ammonia and tetraethyl silicate, stir and mix evenly at room temperature, transfer to an oil bath for heating to obtain a white suspension, then reduce pressure and filter, wash the filter residue with anhydrous ethanol, and vacuum dry to obtain PS-SiO2 powder; S2, mixing chitosan powder, PS-SiO2 powder and acetic acid aqueous solution to obtain system A; S3, mixing sodium hydroxide, anhydrous ethanol and distilled water, stirring until colorless and clear, and cooling to room temperature to obtain system B; S4, adding system A dropwise into system B to form microspheres, filtering, washing with anhydrous ethanol, and drying at room temperature to obtain PS-CS-SiO2 nanocomposite microspheres; S5. Loading Cu on PS-CS-SiO2 nanocomposite microspheres 2+ , and obtained PS-CS-SiO2@Cu nanocomposite microspheres.
3. The method for preparing the nanocomposite microsphere-supported copper catalytic material according to claim 2, characterized in that: The method for preparing the PS monodisperse microsphere powder in step S1 comprises the following steps: S11. Add 2.0-2.5 g of polyvinyl pyrrolidone, 0.4-0.6 g of azobisisobutyronitrile, 20-40 mL of styrene, and 2-5 mL of distilled water to every 80-100 mL of anhydrous ethanol, perform ultrasonic dispersion at room temperature for 0.5-1 h, and stir at 60-100 °C for 18-30 h under inert gas protection to obtain a mixed solution; S12, centrifuging the mixed solution to obtain a precipitate, and washing the precipitate with anhydrous ethanol to obtain PS monodisperse microsphere powder.
4. The method for preparing the nanocomposite microsphere-supported copper catalytic material according to claim 2, characterized in that: In step S1, 0.8-1.0 g of hexadecyltrimethylammonium bromide, 100-150 mL of anhydrous ethanol and 80-120 mL of distilled water are added to every 0.8-1.2 g of PS monodisperse microsphere powder, and after stirring for 0.2-0.5 h, 0.5-1.0 mL of concentrated ammonia water and 0.5-0.8 mL of tetraethyl silicate are added, and the mixture is stirred at room temperature for 4-8 h, heated in an oil bath at 80° C. for 10-18 h, and vacuum dried at 40-60° C. for 10-18 h to obtain PS-SiO2 powder.
5. The method for preparing the nanocomposite microsphere-supported copper catalytic material according to claim 2, characterized in that: In the step S2, 0.4-0.6 g of PS-SiO2 powder and 102 mL of 1-5% v / v acetic acid aqueous solution are added to every 0.8-1.2 g of chitosan; in the step S3, 40-60 mL of anhydrous ethanol and 40-60 mL of distilled water are added to every 10.0-15.0 g of sodium hydroxide.
6. The method for preparing the nanocomposite microsphere-supported copper catalytic material according to claim 2, characterized in that: The preparation method of PS-CS-SiO2@Cu nanocomposite microspheres in step S5 comprises the following steps: S51, placing the PS-CS-SiO2 nanocomposite microspheres obtained in step S4 in a water bath at 40-60°C for 1-2 hours to obtain system C; S52, add 3.0-5.0 g of copper acetate per 40-60 mL of distilled water, stir at room temperature for 4-8 h to obtain system D; S53. Stir and mix system C and system D, adsorb for 4 to 8 hours, filter, rinse with distilled water, and dry to obtain PS-CS-SiO2@Cu nanocomposite microspheres.
7. An application of the nanocomposite microspheres loaded with copper catalytic material according to claim 1, characterized in that: Used to prepare chiral organoboron compounds with the structural formula: Wherein R1 is phenyl or p-fluorophenyl, and R2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; The preparation method of the chiral organoboron compound comprises the following steps: P1. Add 0.24 mmol of biboric acid pinacol ester, 0.5-1.0 mg of Bolm chiral ligand, 2.2-2.9 mg of PS-CS-SiO2@Cu nanocomposite microsphere catalyst and 2 mL of TL-H2O mixed solvent to every 0.2 mmol of reaction substrate, stir for 10-14 hours and then filter under reduced pressure. The filtrate and residue are set aside. P2, the filtrate was extracted with ethyl acetate and saturated brine in sequence, and then the organic phase was dried over anhydrous Na2SO4, filtered under reduced pressure and rotary dried to obtain a crude product; P3, purifying the crude product by thin layer chromatography to obtain a chiral organic boron compound; The reaction substrate structure in step P1 is as follows: Wherein R1 is phenyl or p-fluorophenyl, and R2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; P4. Wash the filter residue with petroleum ether, dry it in vacuum, and then recover the nanocomposite microsphere-loaded copper catalyst for recycling.
8. The use of the nanocomposite microsphere-supported copper catalytic material according to claim 7, characterized in that: The structural formula of the Bolm chiral ligand in step P1 is: 。 9. The use of the nanocomposite microsphere-supported copper catalytic material according to claim 7, characterized in that: Used to prepare chiral hydroxy compounds with the structural formula: Wherein R1 is phenyl or p-fluorophenyl, and R2 is phenyl, 2-thienyl, naphthyl, o-bromophenyl or p-methylphenyl; The preparation method of the chiral hydroxy compound comprises the following steps: (1) Add 240-250 mg of sodium borate tetrahydrate and 5 mL of THF-H2O mixed solvent to the chiral organic boron compound obtained in step P3, stir for 3-6 h, extract with ethyl acetate and saturated brine in sequence, then dry the organic phase with anhydrous Na2SO4, filter under reduced pressure and spin dry; (2) The residue is spin-dried and purified by thin layer chromatography to obtain a chiral hydroxy compound.
10. The use of the nanocomposite microsphere-supported copper catalytic material according to claim 9, characterized in that: The developing solvent used for thin layer chromatography in step (2) is a mixed solvent of PE and EA, wherein the volume ratio of PE:EA is 5:1.